Comparing perineal repairs for rectal prolapse: Delorme versus Altemeier - Faisal, Elagili; Gurland, Brooke H.; Liu, Xiaobo; Church, James Michael; Ozuner, Gokhan (Springer, 2015)
Purpose Data comparing surgical outcomes and quality of life (QOL) following perineal repair of rectal prolapse are limited. The aim of our study was to compare the shortterm outcome and QOL of two perineal procedures in patients with rectal prolapse. Methods All patients with full-thickness rectal prolapse admitted to our institution and undergoing Delorme and Altemeier procedures from 2005 to 2013 were identified using an institutional, IRB-approved rectal prolapse database. Short-term outcomes and QOL were compared. Results Seventy-five patients (93 % female) underwent rectal prolapse surgery: 22 Altemeier and 53 Delorme, mean age 72 ± 15 years. Sixty-six percentage of patients were ASA grade III or IV (Table 1). The median hospital stay was longer in Altemeier’s group [4 (1–44) days vs. 3 (0–14) days; p = 0.01]. After a median follow-up of 13 (1–88) months, the rate of recurrent prolapse was 14 % (n = 11) [Altemeier 2 (9 %) vs. Delorme 9 (16 %) p = 0.071]. Postoperative complication rate was 12 % (n = 9) [Altemeier 5 (22 %) vs. Delorme 4 (7 %), p = 0.04]. There was no mortality. The Cleveland Global Quality of Life scores in each group were 0.6 ± 0.2 and 0.5 ± 0.3, respectively (p = 0.59), and were not changed by the surgery. Conclusions In patients where abdominal repair of rectal prolapse is judged to be unwise, a Delorme procedure offers short-term control of the prolapse with low risk of complications and with reasonable function. In addition patients that recur after a Delorme procedure can undergo another similar transanal procedure without compromising the vascular supply of the rectum.